Comparative studies on melt processable polyimides derived from 2, 3, 3′, 4′-oxydiphthalic anhydride and 2, 3, 3′, 4′-thioetherdiphthalic anhydride. (June 2013) - Zeng, Hongling; Pei, Xueliang; Chen, Guofei; Cao, Lujie; Chen, Liang; Fang, Xingzhong
Two thermoplastic polyimides were controllably synthesized with similar molecular weight from 2, 3, 3′, 4′-oxydiphthalic anhydride (3, 4′-ODPA) or 2, 3, 3′, 4′-thioetherdiphthalic anhydride (3, 4′-TDPA) with 4, 4′-diaminodiphenyl ether (ODA) by a one-step method of m -cresol. The solubility and mechanical properties of these polymers were investigated for comparison. The thermal and melt processable properties of these polymers were examined carefully by differential scanning calorimetry, thermogravimetric analysis (TGA), rheometer and melt index, and so on. It was found that the glass transition temperature ( Tg ) of 3, 4′-TDPA/ODA was about 15°C lower than that of 3, 4′-ODPA/ODA, the melt indices of 3, 4′-TDPA/ODA at different temperatures were higher than those of 3, 4′-ODPA/ODA, while the minimum melt viscosity of 3, 4′-TDPA/ODA was lower than those of 3, 4′-ODPA/ODA. Furthermore, TGA results showed that 3, 4′-TDPA/ODA had different degradation mechanism in air compared with 3, 4′-ODPA/ODA. The long-term thermooxidative stability results showed that 3, 4′-TDPA/ODA had better thermal oxidative stability than 3, 4′-ODPA/ODA at 410°C for 6 h in air, which could be associated with the results of apparent activation energy ( E a ) of polymers calculated by TGA dynamics. The natural bond orbital charge of ethero atoms (S or O), and energy gap of the corresponding model compounds were also obtained by computational simulation to correlate with polymer properties.